Axial behavior of ferrocement confined cylindrical concrete specimens with different sizes. (1st March 2015) - Kaish, A.B.M.A.; Jamil, M.; Raman, S.N.; Zain, M.F.M.
Highlights: Studied the axial behavior of ferrocement confined cylinder with different sizes. Single layer mesh ferrocement cannot provide significant confinement. Atleast two layer mesh needs in ferrocement jacket to provide necessary confinement. A strength model is proposed for ferrocement confined concrete. Abstract: This paper presents an experimental study on the axial behavior of ferrocement confined cylindrical concrete specimens. The present study also intends to investigate the effect of specimen size on the confinement action of ferrocement jacket. Three types of 27 concrete cylinders with diameters of 150, 100, and 75 mm are cast and tested under axial compression. Each type of specimens is confined with single layer and double layer welded wire mesh ferrocement jacket having a constant thickness of the jacket. The experimental results demonstrate the effectiveness of ferrocement confinement in enhancing the strength, ductility and energy absorption capacity of concrete specimens. The confinement action is found more effective in case of smaller specimens. A post-peak descending branch in the axial stress–strain curve is observed in all the confined specimens. The stress–strain behavior and the failure pattern indicate that single layer mesh ferrocement jacket cannot provide significant confinement; at-least two layer mesh is required for substantial confinement. A new analytical model for the strength of ferrocement confined circular concrete specimen is proposed based on the test results of this work and verified with the recent experimental data obtained from the literature.